A Cross-Sectional Analysis of Correlation Between Lipid Profile and HbA1c Among Non-Diabetics, Diabetics and Prediabetics - Gogia, Taruna; Kaushik, Namrata; Jain, Gunjan (National Journal of Medical Research, 2025)
Background: Diabetes mellitus (DM) leads to chronic increase in blood glucose levels which is measured by glycated haemoglobin (HbA1c) levels. Dyslipidaemia also increases risk of DM. Objectives: To identify correlation between HbA1c and lipid profile in normal, prediabetic and diabetic individuals. Methods: A cross-sectional study was conducted for a duration of one month at a tertiary care hospital. Individuals diagnosed with diabetes and pre-diabetes based on their blood glucose levels for the first time were included in the study. Subjects with normal levels of glucose were included for comparison. Pearson correlation test was used to check correlation between HbA1c and lipid profile among three groups. P<0.05 was considered significant. Results: 30 subjects were recruited in each of the three groups. HbA1c, fasting and postprandial blood glucose levels were significantly elevated in diabetic and prediabetic groups as compared to normal subjects (P <0.001). Among the lipid parameters, total cholesterol and triglycerides (TG) were significantly elevated in diabetic groups as compared to normal (P <0.05). Correlation assessment revealed significant weak positive correlation between HbA1c and total cholesterol among diabetics and pre-diabetics and between HbA1c and TG in diabetics (P <0.05). Conclusion: Total cholesterol and TGs are correlated significantly with HbA1c in diabetic patients. Long-term studies must be conducted to understand the chronic implications of this correlation.